Artistic Activism and the Re-enchantment of the World - Oliveira, Luiz Sérgio de (Farol, 2025)
This article seeks to offer some reflections, albeit within an initial approach, regarding the activist turn in contemporary art. To this end, it attempts to trace a genealogy that offers a possible interpretation of what has been configured as the production of activist art, especially that which, presenting itself as "community art," seems to displace the artist to a position of laterality. While the assumptions of a portion of modernist art have long proven totally inefficient and inadequate to deal with the complexities and inequalities of the contemporary world, on the other hand, art still seems to seek the tones and measures so that, guaranteeing its permanence and the relevance of the artists, it can speak to and listen to the world in processes of enchantment of art and life.